Socio-economic determinants of keeping goats and sheep by rural people in southern Benin - Dossa, Luc Hippolyte; Rischkowsky, Barbara; Birner, Regina; Wollny, Clemens (Springer, 2008)
An understanding of factors influencing the decision of rural people to keep sheep and/or goats is crucial when formulating technologies and policies that support village-based small ruminant production. The knowledge of such factors will also improve assessment of impact intervention strategies on the livelihoods of rural people. Structured questionnaires administered in 228 households were used to study the ownership patterns of small ruminants in southern Benin. The ownership of goats was higher (91%) than sheep (35%) because goats are not affected by any ethnic or cultural restrictions. Goats are also perceived to be a less risky to invest into compared to sheep. Women represented 71% of the keepers of goats. Predictive models of ownership were developed using logistic regression. The results showed that younger household members (p < 0.05) especially young women (60%) are more likely to own small ruminants. Owners of small ruminants are less likely to be involved in off-farm activities and would often have no access to credit facilities. Gender, ethnicity, and perception of risk associated with species are the major factors affecting people’s choice of species. These findings highlight the financing and insurance roles that small ruminants, particularly goats, are playing in the study area. In order to develop suitable technologies and formulate policies to improve productivity and enhance livelihoods, the constraints to goat production need to be identified, and the local knowledge of the keepers should be investigated.